Modeling of partial reduction of hematite with carbon-monoxide in tunnel furnace - Salimibani S.; Jafari-Ramiani A.; Firoozi S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
DRI production in tunnel furnaces sometimes encounters an incomplete degree of reduction. A model is required to tackle heterogeneous reaction rates, crucible heat transfer, and oxide morphology. Herein, a three-phase model is proposed based on the heat and mass conservation and reaction kinetics, to describe the reduction of hematite to magnetite in the crucibles. The model was implemented via a Fortran program using finite volume discretization, and the results were validated against available experimental data. The model moderated the uncertainties in the reaction rate with a reformulation considering the solid morphology. The results also revealed that the speed and diameter of the crucible have dominant effects on the overall progress of the reduction by changing the heat transfer rate within the crucible. In contrast, the crucible thickness has a minor effect on the reaction and could be regarded as an economical parameter.